2006
DOI: 10.1007/s10038-006-0007-3
|View full text |Cite
|
Sign up to set email alerts
|

An association between asthma and TNF-308G/A polymorphism: meta-analysis

Abstract: Tumor necrosis factor (TNF) is a potent inflammatory cytokine that contributes to airway inflammation in asthma. Previous studies have reported that a G-to-A transition at position -308 (-308G/A, also referred to as TNF-a-308*1 and 308*2 respectively), is associated with asthma, but other studies have shown conflicting results. To investigate a possible association between the TNF-308G/A polymorphism and asthma, we performed transmission disequilibrium tests and a case-control study (family samples: 495 member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 46 publications
(63 reference statements)
4
27
0
3
Order By: Relevance
“…It also appears that anti-TNF-␣ therapy is most effective in patients with more severe disease, which is consistent with the present study, in which we demonstrated that different levels of TNF-␣ in airways between C57BL/6 and BALB/c mice directly correlated with the intensity of AHR in these strains of mice (47). Furthermore, polymorphisms in the TNF-␣ gene have been associated with asthma severity and risk (2,18,26), and TNF-␣ variants have been shown to lead to altered levels of TNF-␣ protein in patients and were associated with asthma incidence (5,43). These collective findings, along with our present observations, suggest that TNF-␣ may be an important target in the treatment of asthma (19).…”
Section: Discussionsupporting
confidence: 92%
“…It also appears that anti-TNF-␣ therapy is most effective in patients with more severe disease, which is consistent with the present study, in which we demonstrated that different levels of TNF-␣ in airways between C57BL/6 and BALB/c mice directly correlated with the intensity of AHR in these strains of mice (47). Furthermore, polymorphisms in the TNF-␣ gene have been associated with asthma severity and risk (2,18,26), and TNF-␣ variants have been shown to lead to altered levels of TNF-␣ protein in patients and were associated with asthma incidence (5,43). These collective findings, along with our present observations, suggest that TNF-␣ may be an important target in the treatment of asthma (19).…”
Section: Discussionsupporting
confidence: 92%
“…This inversion explains ∼40% of the population-attributable risk for joint susceptibility to obesity and asthma. Additional genes including the β2-adrenergic receptor gene (ADRB2), 148,149 the TNF gene, 150,151 and the lymphotoxin-α (LTA) gene 152,153 have been associated in both obesity and asthma in children. However, the limited number of these studies highlights the paucity of data on genetic susceptibility for obesity-related asthma.…”
Section: Genetics Of Obesity-related Asthmamentioning
confidence: 99%
“…[58]. Nonetheless, genetic polymorphism of the TNF-α gene on chromosome 6 is associated with asthma, asthma severity and BHR [59].…”
Section: Role Of Tnf-α In Asthma and Copdmentioning
confidence: 99%